Applied climatology: Doing the relational work of climate. (August 2014) - Tadaki, Marc; Salmond, Jennifer; Heron, Richard Le
Applied climatology has long been a niche domain, straddling the intersection between the social and natural sciences and populated largely by geographers explicitly interested in reframing human activities around climate. As human-atmospheric relations become increasingly embedded within institutions of governance, new narratives of and for applied climatology are emerging to champion particular atmospheric objects, orientations, practices and institutions into positions of policy relevance and investment priority. This paper attempts to understand these intersecting politics of 'climate and society' research by situating their emergence through three lenses of inquiry. First, we explore the historical disciplinary work of 'application' in geographical climatology, paying particular attention to how 'relevance' has been understood and practised. Second, we reassemble a missed disciplinary conversation about ideology in applied geography, and link this to definitions and rationales for applied climatology. Third, we explore five recent thematic engagements in applied climatology, to generate thinking about the institutions and practices of assembling climate in new circles of 'application', policy and elsewhere. The 'applications' that climatologists choose to pursue – and the ways in which they pursue them – are deeply political questions that reproduce decision-making logics, funding rationalities, notions of expertise and problem framings. In conclusion, we argue that, rather than understanding 'climate' and 'society' as stable entities with standard (e.g. quantitative) practices or modes of association, we might instead concern ourselves with the practices of assembling human-atmospheric relations.